YAMATO 86029: AQUEOUSLY ALTERED AND THERMALLY METAMORPHOSED CI-LIKE CHONDRITE WITH UNUSUAL TEXTURES - Tonui E.R.; Zolensky M.E.; Lipschutz M.E.; Wang M.-S.; Nakamura T. (My University, 2003)
We describe the petrologic and trace element characteristics of the Yamato 86029 (Y-86029) meteorite. Y-86029 is a breccia consisting of a variety of clasts, and abundant secondary minerals including coarse- and fine-grained phyllosilicates, Fe-Ni sulfides, carbonates, and magnetite. There are no chondrules, but a few anhydrous olivine-rich grains are present within a very fine-grained phyllosilicate-rich matrix. Analyses of 14 thermally mobile trace elements suggest that Y-86029 experienced moderate, open-system thermal metamorphism. Comparison with data for other heated carbonaceous chondrites suggests metamorphic temperatures of 500–600°C for Y-86029. This is apparent petrographically, in partial dehydration of phyllosilicates to incompletely re-crystallized olivine. This transformation appears to proceed through ‘intermediate’ highly-disordered ‘poorly crystalline’ phases consisting of newly formed olivine and residual desiccated phyllosilicate and their mixtures. Periclase is also present as a possible heating product of Mg-rich carbonate precursors. Y-86029 shows unusual textures rarely encountered in carbonaceous chondrites. The periclase occurs as unusually large Fe-rich clasts (300–500 μm). Fine-grained carbonates with uniform texture are also present as small (10–15 μm in diameter), rounded to sub-rounded ‘shells’ of ankerite/siderite enclosing magnetite. These carbonates appear to have formed by low temperature aqueous alteration at specific thermal decomposition temperatures consistent with thermodynamic models of carbonate formation. The fine and uniform texture suggests crystallization from a fluid circulating in interconnected spaces throughout entire growth. One isolated aggregate in Y-86029 also consists of a mosaic of polycrystalline olivine aggregates and sulfide blebs typical of shock-induced melt re-crystallization. Except for these unusual textures, the isotopic, petrologic and chemical characteristics of Y-86029 are quite similar to those of Y-82162, the only other heated CI-like chondrite known. They were probably derived from similar asteroids rather than one asteroid, and hence may not necessarily be paired.